Dissent and Displacement of Subalternity in Malayalam Cinema: A Cultural Analysis of Papilio Buddha by Jayan K. Cherian - Sony Jalarajan Raj; Swapna Gopinath and Rohini Sreekumar (Journal of Creative Communications, 2016)
The theme of subalternity with its inherent ramifications is yet to find favour among film makers in India. Progressive film makers of the 1960s attempted to address the theme of subaltern and dared to give the subaltern a voice, but they remained singular attempts. Through a case study on a Malayalam film (a regional film industry from the state of Kerala in India) Papilio Buddha this article tries to analyze the representation of Dalit community in Indian cinema. Though Malayalam film industry has tried to address the concern of Dalits, they have been stereotyped in many ways and reduced to being sidekicks to villains or unskilled labourers having no identity. They remained as instruments to idolize the hero, to act as a contrast to the elite protagonist or as the poor helpless victims who offer the protagonist an opportunity to display his heroism. Papilio Buddha grabbed media attention when it was denied clearance by the censor board as it explores the territory of Dalit consciousness by focusing the lens on the land strike by the Dalit communities and creating a counter narrative to the hitherto idealized images created by the state.